2009
DOI: 10.1364/oe.17.020465
|View full text |Cite
|
Sign up to set email alerts
|

Electric currents induced by twisted light in Quantum Rings

Abstract: We theoretically investigate the generation of electric currents in quantum rings resulting from the optical excitation with twisted light. Our model describes the kinetics of electrons in a two-band model of a semiconductor-based mesoscopic quantum ring coupled to light having orbital angular momentum (twisted light). We find the analytical solution, which exhibits a "circular" photon-drag effect and an induced magnetization, suggesting that this system is the circular analog of that of a bulk semiconductor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…The research in TL spans several areas, such as the generation of beams [4,5], the interaction of TL with atoms and molecules [6,7] or with condensed matter [8][9][10][11][12][13][14][15][16][17][18][19][20]. TL has already proved to be useful in applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research in TL spans several areas, such as the generation of beams [4,5], the interaction of TL with atoms and molecules [6,7] or with condensed matter [8][9][10][11][12][13][14][15][16][17][18][19][20]. TL has already proved to be useful in applications.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in other fields are also sought, for example in quantum information technology, where the OAM adds a new degree of freedom encoding more information [24][25][26][27]. In addition, theoretical studies in solid state physics predict, for instance, that TL can induce electric currents in quantum rings [19], and new electronic transitions (forbidden for plane waves) in quantum dots [18]. This all suggests that TL can be a new powerful tool to control quantum states in nanotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The new light source well-merged with powerful control technique in time or frequency domain such as femtosecond technology enables us to carry out experiments for high-intensity field physics [4], ultrafast nonlinear spectroscopy [5][6][7], terahertz vortex generation based on radiation from coherently-accelerated charged particles along the azimuthal direction [8]. Recently, opticalvortex light sources by the use of femtosecond pulses were reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Bh, 78.20.Ls, 78.40.Fy, 42.50.Tx Light with orbital angular momentum (OAM), referred to as twisted light, is a relatively new field of research which has become increasingly popular [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] since Allen et al showed how twisted light beams can be easily generated from conventional laser beams [18]. Recently, the theoretical foundation of the optical excitation of solids and nanostructures with twisted light has been established [19][20][21][22][23][24][25][26][27], and experimental studies with twisted light on semiconductors have been carried out [28,29].One motivation for such studies is the prospect of using the large amounts of angular momentum that twisted light can carry in order to control the spin dynamics of electrons, thus adding a flexible tool to the active field of spin control [30][31][32][33][34][35][36][37][38][39]. In this context two different mechanisms need to be distinguished.…”
mentioning
confidence: 99%
“…Recently, the theoretical foundation of the optical excitation of solids and nanostructures with twisted light has been established [19][20][21][22][23][24][25][26][27], and experimental studies with twisted light on semiconductors have been carried out [28,29].…”
mentioning
confidence: 99%